Independence And Learning Achievement Of Positions Between Lines Through Youtube Digital Learning Media SDSK Marie Joseph - Kusuma, Irsandi; Yani T, Ahmad; Sayu, Silvia (JPMI (Jurnal Pendidikan Matematika Indonesia), 2023)
This research aims to determine the increase in independence and learning achievement with YouTube videos as digital learning media at SDSK Marie Joseph Pontianak. The research method used in this research is quantitative experimental research. The population and sample in this study were class IV students with research instruments using questionnaires, pre-test and post-test questions. The data analysis techniques used in this research are descriptive data, prerequisite testing, hypothesis testing. The research results show that; (1) The Let's Learn YouTube video as a digital learning medium can increase learning independence in class IV cross-line position material at SDS K MAlRIE JOSEPH Pontianak. It is proven from the calculation results that as can be seen from the average value of student learning independence at the beginning, it was 72.208, increasing to 103.916. (2) The Let's Learn YouTube video as a digital learning medium can improve learning achievement in class IV inter-line position material at SDS K MAlRIE JOSEPH Pontianak in class IV inter-line relationship material. It is proven by the results of the calculations that as can be seen the average pre-test learning achievement score for experimental class students in the Pre-Test is 64.25 and the Post-Test learning achievement is 77.167. (3) The Let's Learn YouTube video as a digital learning medium can collectively increase the learning independence and achievement of Class IV SDSK MARIE JOSEPH Pontianak students. It can be seen in the Multivariate Anova test or F Test, namely a sig value < 0.005 indicating that the test results can jointly improve learning independence and learning achievement using the Multivariate Anova Test (Manova) or F Test.